2000
DOI: 10.1002/1522-726x(200012)51:4<407::aid-ccd7>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Rotational atherectomy or balloon angioplasty in the treatment of intra-stent restenosis: BARASTER Multicenter Registry

Abstract: The BARASTER registry was formed to evaluate the initial success and long-term results of rotational atherectomy in the management of in-stent restenosis. Rotational atherectomy was used in 197 cases of in-stent restenosis: 46 with stand-alone rotational atherectomy or at most 1 atmosphere of balloon inflation (Rota strategy), and 151 with rotational atherectomy and adjunctive balloon angioplasty <1 atmosphere (Combination strategy). These were compared with 107 episodes of in-stent restenosis treated with bal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 23 publications
1
10
0
1
Order By: Relevance
“…However, when the actual delivered dose to the target tissues was simulated, a considerable discrepancy was appreciated between the prescribed and delivered dose, 10 which necessitates precise investigations of vascular responses that are based on the actual delivered dose. Thus, the aims of the present study were to (1) investigate the relationship between the delivered dose and vascular changes individually by volumetric intravascular ultrasound (IVUS) analysis and (2) test the appropriateness of the current dose-prescription protocol for 90 Sr/Y radiation to native ISR lesions.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…However, when the actual delivered dose to the target tissues was simulated, a considerable discrepancy was appreciated between the prescribed and delivered dose, 10 which necessitates precise investigations of vascular responses that are based on the actual delivered dose. Thus, the aims of the present study were to (1) investigate the relationship between the delivered dose and vascular changes individually by volumetric intravascular ultrasound (IVUS) analysis and (2) test the appropriateness of the current dose-prescription protocol for 90 Sr/Y radiation to native ISR lesions.…”
supporting
confidence: 88%
“…Although several aggressive strategies for ISR treatment, such as dilation and debulking, have altered late outcomes, the actual recurrent restenosis rates remain high. 1,2 Recently, intravascular brachytherapy (IVBT), as a potential antiproliferative treatment, has been applied to ISR and has demonstrated a striking reduction in recurrent restenosis. [3][4][5] This new technology has been approved and is currently being used worldwide.…”
mentioning
confidence: 99%
“…The findings of the various studies have created some general guiding rules for the optimized use of RotA (Brown et al, 1997;Reifart et al, 1997;Whitlow et al, 2001;Dill et al, 2000;Buchbinder et al, 2001;vom Dahl J et al, 2002;Goldberg et al, 2000):…”
Section: Rota-general Conceptsmentioning
confidence: 99%
“…Volumes were then divided by length to create an index (ie, stent, lumen, and IH volume index); results are reported as mm 2 . The axial variability in IH reaccumulation was assessed by calculating the coefficient of variation of the increase in IH for each segment by dividing mean IHϫ100 by the standard deviation of IH.…”
Section: Intravascular Ultrasound Imaging and Analysismentioning
confidence: 99%
“…1,2 Conversely, recent studies of adjunctive intravascular brachytherapy (IVBT) have shown a striking improvement in long-term outcomes. 3 4 5 In the early IVBT trials, late stent thrombosis occurred in 5% to 10% of patients and was associated with fresh stent deployment and early discontinuation of antiplatelet therapy.…”
mentioning
confidence: 99%